Impact of human resource management systems, knowledge management effectiveness and human resource information system on organisational performance in Jordanian national banks - Altarawneh, Rania Jamal Saleh
The financial industry in Jordan is highly competitrve, whereby many banks are competing among themselves for growth and survival in the business world. Thus, organizational performance is critical to their survivability. Banks invest in their human resources management, knowledge, and technology to improve their performance. The performances of national banks in Jordan heavily rely on their human resource. The latest reports of the Central Bank of Jordan and the Association Banks of Jordan revealed that the human resources management systems are ineffective on enhancing banks performance. This may result in revisit the role of banks as a critical pillar of the Jordanian economy. This study was conducted to examine the manager's perceptions from national banks about their human resource management systems and knowledge management effectiveness and how it impacts their performance. In this study, human resource management systems act as the independent constructs, while organization performance serves as the dependent variable. Knowledge management effectiveness has been identified as the mediating factor in the relationship between human resource management systems and organizational performance. Also, the human resource information system has been identified as the moderator on the relationship between knowledge management effectiveness and organization performance.This study employs quantitative research. The population of this study consists of 756 branches of national banks serving in Jordan whereby each branch represented by one manager. A self-administered questionnaire is used to collect a response from managers in each bank. By using simple random sampling and a total of 384 copies of the questionnaire were distributed, 375 were returned which equivalent to 98% of the respondent rate. The framework of the study is tested using structural equation modeling (AMOS-SEM). Hypothesis testing is done by z-test for testing the path coefficient of the direct effect and indirect effect in the model confirm with bootstrapping and multi-group confirmatory factor analysis.Findings of this study showed that human resources management systems have an impact on organization performance with knowledge management effectiveness as a mediator with R2 was 0.56. The study also found that the human resource information system plays the role of moderator between knowledge management effectiveness and organization performance.This study will benefit bank managers to enhance their performance by improving their human resource management system. The suitable system may improve knowledge management effectively in the organization. The system also works as a technological factor in moderating the environment of the banks.